Analysis of Coronavirus Spreading Uses The CRISP-DM as A Framework: Predictive Modeling - Muhammad Akbar Rivai, Dewo Wishnu Setya Kusuma, Egi Pahlevi Ramadhan, Emil R. Kaburuan, Tuga Mauritsus (International Journal of Advanced Science and Technology, 2020)
Coronaviruses (CoVs), which are indicated by sensory-positive RNA viruses, have a sign with a crown shape projected from the surface of the RNA genome to look very large, also have unique replication. Coronavirus causes various diseases in mammals, birds ranging from enteritis in cattle, pigs, and chickens. Corona has problems such as respiratory diseases for infections in humans that cause death in infected R & D. In this study. We provide a brief introduction about Coronavirus that discusses the predictive results (uses the CRISP-DM as a framework) of spreading the Corona Virus to any country. We will also consider an outbreak of Coronavirus where the results we have found will find a solution for the future so that this virus does not spread widely to various countries.